2015
DOI: 10.1007/s11239-015-1191-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported health preferences of anticoagulant-related outcomes

Abstract: Strokes can have a catastrophic impact on patients' health-related quality of life (HRQoL). In addition to warfarin, two novel oral anticoagulants, i.e., dabigatran and rivaroxaban, have been approved to prevent strokes. This study aimed to use direct measures to elicit patient-reported utilities (i.e., preferences) for anticoagulant-related outcomes. A cross-sectional survey was administered to 100 patients taking warfarin in an anticoagulation clinic. Utilities for six long-term and four short-term anticoagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…2) [18, 4049]. Three of these could be characterised as multicentre studies ensuring a representative inclusion of patients and applying a methodology that addressed most of the known differences between VKAs and NOACs (mean number of patients 426) [4042].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) [18, 4049]. Three of these could be characterised as multicentre studies ensuring a representative inclusion of patients and applying a methodology that addressed most of the known differences between VKAs and NOACs (mean number of patients 426) [4042].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, three single-centre studies including a convenience sample of AF patients (100 % OAC users; mean number of patients 118) mostly used a standard gamble/trade-off technique (two studies), while one study used a preference questionnaire [4749]. None of these studies addressed all known differences between NOAC or VKA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…96,113-117 Among cancer patients, risk of bleeding was less important than ensuring that VTE prophylaxis did not interfere with cancer treatment and OAC efficacy. 118,119 Studies assessing patient preferences toward VKAs versus NOACs 105, [120][121][122][123][124][125][126][127][128][129] indicate that when efficacy and safety are similar, patients with AF and VTE commonly favored simpler, more convenient treatment regimens, less frequent dosing, fixed-dose medication, without need for regular monitoring or bridging, or drug-food interactions. 103,111,112,117,121,[130][131][132][133][134][135]…”
Section: Patient Values and Preferencesmentioning
confidence: 99%
“…HRQoL was reported in 5 studies and used the Euro-QoL utility and visual analogue scores, which covered 5 dimensions (consisting of mobility, autonomy, usual activities, pain/discomfort, anxiety/ depression) or the Sawicki questionnaire (which is a 32-item questionnaire grouped covering general treatment satisfaction, self-efficacy, strained social network, daily hassles and distress). 14,46,47 The majority of the studies (14 studies) described: patient-reported treatment satisfaction, which had been measured using the ACTS (a 15-point scale to score burden and benefit); or treatment satisfaction questionnaire for medication (TSQM) version II, which assesses 4 subscales of on Likert scales) 15,16 ; and medication-related, review or interventionrelated, and adverse outcomes. Overall, the outcomes were diverse with differing definitions, methods of data collection, varying time points and different reporting methods.…”
Section: Study Outcomesmentioning
confidence: 99%
“…13 HRQoL can be defined as an evaluation of impairment, disability or handicap. 12,14 Patient satisfaction determines perceived burden or benefits of the perceived treatment being appraised. 12 The Anti-Clot Treatment Scale (ACTS), Treatment Satisfaction Questionnaire for Medication (TSQM) and Perception of Anticoagulation Questionnaire (PACT) are tools used to assess satisfaction.…”
mentioning
confidence: 99%